PERBANDINGAN ANTARA TAMU HOTEL INDONESIA GENERASI X DAN Y TERHADAP NIAT KESETIAAN LUMINOR HOTEL PECENONGAN DI JAKARTA - Angelica, Angelica; Youn, Chun Hee; Chyntya, Dhea; Situmorang, Jimmy M. H. (Jurnal Ilmiah Pariwisata; Vol 24 No 2 (2019): Jurnal Ilmiah PariwisataDO - 10.30647/jip.v24i2.1305, 2019)
The rapid growth of tourism as both activity and its economic is getting more competitive, interconnected, focused, rapidly evolving. As people travel to and from all parts of the world seeking a variety of experiences and they have the right to expect professional services from the accommodation they choose. In this research, researchers will measure how perceived hotel quality will affect loyalty intentions of the hotel guest of Luminor Hotel Pecenongan. The sample was purposive non-probability sampling. The respondents are 100 hotel guests. The collected data will be processed by SPSS software. The result indicates that generation X is value-centered in building loyalty and place more focus on facilities and convenience. Whereas, generation Y exhibits both value and quality on room and service and convenience. The investigation shed light on future research in tourism and hospitality to study the characteristic of current generation. The particular objectives are to identify attribute-based hotel quality and execute performance improvement areas for each generation in Luminor Hotel Pecenongan. This study supports theory on generational behaviors and provides managerial insights to Luminor Hotel Pecenongan.